1996
DOI: 10.1097/00003246-199603000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to reposition vasopressors and inotropes in sepsis?

Abstract: Insufficient evidence exists to support goal-directed therapy with vasopressors and inotropes in the treatment of sepsis syndrome. No definitive recommendations can be made about the superiority of a vasopressor or inotropic agent due to the lack of data. However, it may be that evaluation of vasopressors earlier in sepsis syndrome will yield more promising results. Large, comparative, controlled trials assessing mortality rate and development of multiple organ system dysfunction are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 62 publications
1
40
0
5
Order By: Relevance
“…132 Deleterious effects associated with vasopressor agents include the development of splanchnic hypoperfusion, excess tachycardia and coronary ischemia. 133 Existing evidence has not definitively proven one vasopressor agent superior to another in the setting of severe sepsis or septic shock. 133 Some definitive evidence on the current role of vasopressin and its effect on outcome is expected from the Canadian multicentre Vasopressin and Septic Shock Trial, VASST.…”
Section: Vasoactive Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…132 Deleterious effects associated with vasopressor agents include the development of splanchnic hypoperfusion, excess tachycardia and coronary ischemia. 133 Existing evidence has not definitively proven one vasopressor agent superior to another in the setting of severe sepsis or septic shock. 133 Some definitive evidence on the current role of vasopressin and its effect on outcome is expected from the Canadian multicentre Vasopressin and Septic Shock Trial, VASST.…”
Section: Vasoactive Agentsmentioning
confidence: 99%
“…133 Existing evidence has not definitively proven one vasopressor agent superior to another in the setting of severe sepsis or septic shock. 133 Some definitive evidence on the current role of vasopressin and its effect on outcome is expected from the Canadian multicentre Vasopressin and Septic Shock Trial, VASST.…”
Section: Vasoactive Agentsmentioning
confidence: 99%
“…The literature provides little guidance on the choice of vasoactive agents to maintain an adequate mean arterial pressure without further constricting kidney vessels (77). Clearly, ␣-adrenergic agents cause renal vasoconstriction and therefore can prevent recovery from ATN.…”
Section: Hemodynamic Supportmentioning
confidence: 99%
“…Our finding was also supported by Rudis, Basha, Zarowitz. [12] They performed a MEDLINE search from 1985 to 1994 relating to all pertinent English and French articles dealing with hemodynamic support with selected vasopressors and inotropic agents in human sepsis and sepsis syndrome and found that epinephrine and norepinephrine uniformly increased hemodynamic values. Similar to the study of Bollaert et al, [13] where epinephrine was effective in attaining MAP even in patients in whom dopamine had failed, our study also lends accreditation to the fact that epinephrine is a very effective vasopressor but there are three concerns regarding the use of epinephrine, 1) epinephrine increases myocardial oxygen demand; (2) epinephrine increases serum glucose and lactate, [14] which is largely a calorigenic effect (increased release and anaerobic breakdown of glucose); and (3) epinephrine appears to have adverse effects on splanchnic blood flow.…”
Section: Discussionmentioning
confidence: 99%